2000
DOI: 10.1152/jappl.2000.88.6.2246
|View full text |Cite
|
Sign up to set email alerts
|

Effects of length oscillation on the subsequent force development in swine tracheal smooth muscle

Abstract: It has been shown that deep inspiration (DI) taken before application of bronchoconstricting stimuli causes a reduction in the subsequent bronchoconstriction; a fast DI has a greater inhibitory effect than a slow DI. We hypothesize that periodic length changes imposed on a relaxed airway smooth muscle (ASM) would attenuate subsequent bronchoconstriction by disrupting the organization of the contractile apparatus, and this could be an important mechanism for the observed bronchoprotective effect of DI and tidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
146
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(155 citation statements)
references
References 14 publications
8
146
0
1
Order By: Relevance
“…Response of resting ASM to mechanical perturbation It was mentioned briefly previously that length oscillation applied to ASM in the relaxed state has been found to have an inhibitory effect on the muscle's ability to generate force in the subsequent contractions [69]. The same study also revealed that the inhibitory effect was linearly correlated to the amplitude and duration of oscillation, but was relatively independent of oscillation frequency.…”
Section: In Vitro Behaviour Of Asmmentioning
confidence: 77%
See 2 more Smart Citations
“…Response of resting ASM to mechanical perturbation It was mentioned briefly previously that length oscillation applied to ASM in the relaxed state has been found to have an inhibitory effect on the muscle's ability to generate force in the subsequent contractions [69]. The same study also revealed that the inhibitory effect was linearly correlated to the amplitude and duration of oscillation, but was relatively independent of oscillation frequency.…”
Section: In Vitro Behaviour Of Asmmentioning
confidence: 77%
“…observed to diminish the muscle's ability to generate force in the subsequent contractions [69]. It was postulated by KING et al [26] that this post-oscillation refractoriness of resting ASM was responsible for the bronchoprotective effect of deep inspiration taken before bronchoprovocation seen in nonasthmatics, and that in asthmatics, this refractoriness might be absent.…”
Section: Evidence Of Asm Involvement In Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the maximal force-generating capacity of ASM during or immediately following these oscillations is also reduced (66,84,85,128,186,198,242). The decline in isometric force that ensues length oscillations has been shown to be proportional to the amplitude and the duration of the stretch, but not to the frequency (242). These results demonstrated that the force produced by ASM in response to a given stimulus is greater in a static environment than a dynamic environment.…”
Section: Muscle Factorsmentioning
confidence: 83%
“…Nevertheless, these length oscillations are known to decrease ASM stiffness, even during supra-maximal activation with ACh (66,84,128,198). Importantly, the maximal force-generating capacity of ASM during or immediately following these oscillations is also reduced (66,84,85,128,186,198,242). The decline in isometric force that ensues length oscillations has been shown to be proportional to the amplitude and the duration of the stretch, but not to the frequency (242).…”
Section: Muscle Factorsmentioning
confidence: 99%